Prevalence of Neisseria meningitidis carriers in children under five years of age and teenagers in certain populations of Mexico City Prevalencia de portadores de Neisseria meningitidis en niños menores de cinco años de edad y adolescentes en determinadas poblaciones de la Ciudad de México - Luz Elena Espinosa de los Monteros; Felipe Aguilar-Ituarte; Leticia Verónica Jiménez-Rojas; Pablo Kuri; Romeo S Rodríguez-Suárez; Demóstenes Gómez-Barreto (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To carry out a pilot study to discover the frequency of colonization in healthy children under five years old and teenagers, as well as the distribution of the different N. meningitidis serogroups isolated from nasopharyngeal samples collected from the population under study. MATERIAL AND METHODS: The population included youth between 15 and 19 years old living in social rehabilitation centers (SRC) and university teenagers (UT) as well as children under the age of five attending day care centers (DCC) in Mexico City. Nasopharyngeal exudates were processed using standard microbiological techniques in order to identify Nm, the serogroup, type and subtype of these isolates. RESULTS: A total of 2 310 samples (774 SRC, 800 UT and 736 DCC) were taken. Total prevalence of Nm was 1.6 per cent. In teenagers living in SRC the prevalence was 2.9%. The most frequent serogroups were Y (29.7%), C (24.3%) and B (10.8%). CONCLUSIONS: The prevalence of carriers in the study environment was significant (1.6%) and similar to countries in which the invasive illness is much more frequent. OBJETIVO: Realizar un estudio piloto que permita conocer la frecuencia de colonización en niños sanos menores de cinco años y adolescentes, así como la distribución de serogrupos de los aislamientos de Neisseria meningitidis (Nm) obtenidos de la nasofaringe de la población estudiada. MATERIAL Y MÉTODOS: Se incluyeron, jóvenes entre los 15 y 19 años de edad, de centros de readaptación social (CRS) y adolescentes universitarios (AU), así como niños menores de cinco años que asisten a estancias infantiles (EI) en la Ciudad de México. Se tomaron exudados nasofaríngeos y fueron procesados, usando las técnicas microbiológicas clásicas, para identificar Nm, serogrupo, tipo y subtipo de estos aislamientos. RESULTADOS: Se incluyeron un total de 2310 muestras (774 CRS, 800 AU y 736 EI). La prevalencia total de Nm fue 1.6% y en los adolescentes de CRS fue 2.9 por ciento. Los serogrupos más frecuentes son; Y (29.7%), C (24.3%) y B (10.8%). CONCLUSIÓN: La prevalencia de portadores en nuestro medio fue significativa (1.6%) y similar a los países en los que la enfermedad invasiva es mucho más frecuente.